Neuroprotective effect of diet restricted preconditioning on cerebral ischemia in mice - Altunay, Serdar; Dalay, Arman; Dilden, Aysun; Sertel, Elif; Balçıkanlı, Zeynep; Tancan, Emre; Karaçay, Reyda; Kılıç, Ertuğrul (Wiley, 2017)
[Abstract Not Available]
Keywords: Neuroprotective Effect; Cerebral Ischemia; Ndiet Restricted